Postcode health inequalities in aortic valve surgery in North East England: retrospective study of disparities in presentation and hospital outcomes - Benjamin Irene Omoregbee; Emeka B. Kesieme; Dumbor L. Ngaage (BMJ Public Health)
Introduction Variations and avoidable differences in healthcare between different geographical regions cause health inequality. Postcode lottery in population health could have implications for management of aortic valve disease, for which surgery is the standard of care. We examine disparities in the presentation and outcome of aortic valve replacement (AVR) between three postcode towns in North East England.Methods Clinical data for all patients who had AVR±other procedures at our institution between February 1999 and October 2022 were reviewed. Excluding those from outside our catchment area, we grouped patients according to their postcode towns, namely: Kingston upon Hull (HU), Doncaster (DN) and York (YO), with corresponding health index scores of 77.5, 91.5 and 105.2. We obtained the index of multiple deprivation (IMD) for the postcode towns and compared clinical presentation and in-hospital outcomes between the postcode towns and IMD deciles for their neighbourhoods.Results There were 4639 patients (HU=1699, YO=1736, DN=1204). Compared with other postcode towns, more HU patients were unemployed and active smokers, and they often presented with advanced symptoms, cardiac failure and higher predicted operative risk. They also often underwent urgent or emergency operations and had longer postoperative hospital stays. However, in-hospital mortality was similar for patients from the three postcode towns. By IMD ranking, HU had the most deprived neighbourhood. Multivariable analysis did not identify postcode town or IMD decile as predictors of in-hospital mortality.Conclusions There are disparities in the clinical presentation and outcomes of AVR between the three postcode towns in North England which align with the level of multiple deprivation. These findings support postcode health inequalities in the surgical management of aortic valve disease and warrant policy-directed changes to enhance public awareness and timely access for aortic valve disease management.